2019
DOI: 10.1104/pp.19.01060
|View full text |Cite
|
Sign up to set email alerts
|

The Calmodulin-Binding Protein IQM1 Interacts with CATALASE2 to Affect Pathogen Defense

Abstract: Calmodulin (CaM) regulates plant disease responses through its downstream calmodulin-binding proteins (CaMBPs) often by affecting the biosynthesis or signaling of phytohormones, such as jasmonic acid (JA) and salicylic acid. However, how these CaMBPs mediate plant hormones and other stress resistance-related signaling remains largely unknown. In this study, we conducted analyses in Arabidopsis (Arabidopsis thaliana) on the functions of AtIQM1 (IQ-Motif Containing Protein1), a Ca 21-independent CaMBP, in JA bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…cinerea , and the suppression of AtCAT by SA regulates endogenous H 2 O 2 level and further sulphenylation of tryptophan synthetase β subunit 1, so as to regulate auxin level and disease resistance to Pseudomonas syringae (Yuan et al ., 2017). In addition, AtCAT2 interacts with calmodulin‐binding protein 1 (AtIBP1) to affect pathogen defence response (Lv et al ., 2019). Herein, MeRAV5 interacted with MeCAT1 to inhibit its activity, so as to negatively regulate endogenous H 2 O 2 level and further improve disease resistance.…”
Section: Discussionmentioning
confidence: 99%
“…cinerea , and the suppression of AtCAT by SA regulates endogenous H 2 O 2 level and further sulphenylation of tryptophan synthetase β subunit 1, so as to regulate auxin level and disease resistance to Pseudomonas syringae (Yuan et al ., 2017). In addition, AtCAT2 interacts with calmodulin‐binding protein 1 (AtIBP1) to affect pathogen defence response (Lv et al ., 2019). Herein, MeRAV5 interacted with MeCAT1 to inhibit its activity, so as to negatively regulate endogenous H 2 O 2 level and further improve disease resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Calmodulins (CaM) have been reported to be involved in plant defense responses (Kim et al, 2002;Kang et al, 2006). A Ca 2+ -independent calmodulin-binding proteins (CaMBP) affected defense against the B. cinerea in Arabidopsis (Lv et al, 2019). NtCaM1, NtCaM2 and NtCaM13 were induced by tobacco mosaic virus (TMV)-mediated hypersensitive reaction in tobacco (Takabatake et al, 2007).…”
Section: Defense Related Genes Involved In Response To Botrytis Infecmentioning
confidence: 99%
“…In this study, we identified CAT2-N, not CAT2-C, as an accelerator for JA biosynthesis during plant resistance to B. cinerea through interacting with and promoting ACX2/3. In addition, mutation of the crucial active amino acids of CAT2, including His65, Val106, Phe143, and Tyr348, resulted in extremely low catalase activity for H 2 O 2 degradation, while these mutated CAT2 proteins still interacted with ACX2 and ACX3, and stimulated their ACX activity (Figure 2), further supporting that CAT2 promotes ACX activity at B. cinerea B05.10 than the wildtype plant (Lv et al, 2019). AtIQM1 interacts with and promotes CAT2 activity, especially in the presence of calmodulin5 (CaM5) in Arabidopsis, increasing the activity of the JA biosynthetic enzymes ACX2 and ACX3 (Lv et al, 2019).…”
Section: Discussionmentioning
confidence: 69%
“…A recent report showed that a loss‐of‐function mutant of AtIQM1 ( IQ‐Motif Containing Protein1 ), iqm1‐1 , exhibited higher resistance to biotrophic Pst DC3000 but susceptibility to necrotrophic B . cinerea B05.10 than the wildtype plant (Lv et al, 2019 ). AtIQM1 interacts with and promotes CAT2 activity, especially in the presence of calmodulin5 (CaM5) in Arabidopsis , increasing the activity of the JA biosynthetic enzymes ACX2 and ACX3 (Lv et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation